Effect of carbon nanotube loadings on supercapacitor characteristics. (12th August 2014) - Huang, Naibao; Kirk, Donald W.; Thorpe, Steven J.; Liang, Chenghao; Xu, Lishuang; Li, Wan; Zhang, Shuchun; Sun, Min
Summary In order to improve the properties of electrodes based on carbon nanotubes (CNTs), nanocomposite electrodes of CNTs/activated carbon (AC) are prepared. The effect of CNT loadings on the performance of the nanocomposite electrodes is evaluated by electrochemical methods. Scanning electron microscopy images show the CNTs are well dispersed, entwine with the AC, and form a more conductive network in a nanocomposite electrode. When CNT loadings increase from 0 to 10 wt%, the capacitance increases by 15% (89.4 to 102.5 F g−1), and the equivalent series resistance (ESR) decreases by 13% (0.93 to 0.81 Ω). The capacitance improvement has an optimum CNT loading of about 6 to 10 wt%. The decreased ESR with high CNT loadings does not prevent capacitance loss at sweep rates greater than 50 mV s−1. The nanocomposite electrode shows good cycle performance with no capacity loss after 5000 cycles at a scan rate of 500 mV s−1. These results indicate that the CNT‐based nanocomposite electrodes would be a promising material for use in supercapacitors. Copyright © 2014 John Wiley & Sons, Ltd.